Diagnostic testing holds the key to NTD elimination. - Catharina Boehme; Sergio Carmona; Sarah Nogaro; Mwelecele Malecela (Public Library of Science (PLoS), 2021)
"Fit-for-purpose" diagnostic tests have emerged as a prerequisite to achieving global targets for the prevention, control, elimination, and eradication of neglected tropical diseases (NTDs), as highlighted by the World Health Organization's (WHO) new roadmap. There is an urgent need for the development of new tools for those diseases for which no diagnostics currently exist and for improvement of existing diagnostics for the remaining diseases. Yet, efforts to achieve this, and other crosscutting ambitions, are fragmented, and the burden of these 20 debilitating diseases immense. Compounded by the Coronavirus Disease 2019 (COVID-19) pandemic, programmatic interruptions, systemic weaknesses, limited investment, and poor commercial viability undermine global efforts-with a lack of coordination between partners, leading to the duplication and potential waste of scant resources. Recognizing the pivotal role of diagnostic testing and the ambition of WHO, to move forward, we must create an ecosystem that prioritizes country-level action, collaboration, creativity, and commitment to new levels of visibility. Only then can we start to accelerate progress and make new gains that move the world closer to the end of NTDs.